A review on climate changes towards oil palm production / Noor Sharinie Shari - Shari, Noor Sharinie (Faculty of Plantation and Agrotechnology, 2017)
Changes in climate will increase and decrease oil palm yield and can affect the economic because Malaysian as a largest exporter of palm oil. However, it essential to study the production pattern of palm oil in relation with climate and to making estimation of response palm oil changes in climatic factors such as temperature, precipitation and daylight duration. According to Basiron (2007), show optimum yield related to maximum rainfall need is 1500- 2000 mm year with obscene dry season and sunshine distributed exceed 2000 ha/year. Then, maximum temperature 29 to 33 ℃ and minimum temperature 22 to 24 ℃ favor the increase oil palm. According to MPOC (2012) reported that, current CPO is 45 MN tonnes while El Nino induce drought can decrease 20 % and will out 6 million tonnes of CPO. Furthermore, MPOB (2010), review that economic and development because the direct and indirect of climate changes when CPO drop by 3.3 % to 16.99 MT from 17 MT in 2009. For example, peninsular Malaysian and Sabah both decrease 6.1 and 2.5 % from 9.5 % and 3 MT but in Sarawak CPO production has increase 9.3 % to 2.2 MT.